2018
DOI: 10.1111/dom.13394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ipragliflozin as an add‐on therapy to sitagliptin and metformin in Korean patients with inadequately controlled type 2 diabetes mellitus: A randomized controlled trial

Abstract: AimTo evaluate the efficacy and safety of ipragliflozin vs placebo as add‐on therapy to metformin and sitagliptin in Korean patients with type 2 diabetes mellitus (T2DM).MethodsThis double‐blind, placebo‐controlled, multi‐centre, phase III study was conducted in Korea in 2015 to 2017. Patients were randomized to receive either ipragliflozin 50 mg/day or placebo once daily for 24 weeks in addition to metformin and sitagliptin. The primary endpoint was the change in glycated haemoglobin (HbA1c) from baseline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Of the 22 089 hits retrieved from our search, 144 studies met our inclusion criteria (Figure ). An agreement value ( κ ) of 80% was achieved for studies requiring detailed analysis and extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 089 hits retrieved from our search, 144 studies met our inclusion criteria (Figure ). An agreement value ( κ ) of 80% was achieved for studies requiring detailed analysis and extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all (140/144) studies reported on drop‐out rates between treatment arms. Of these, one third of studies (42/140 or 30%) were considered high risk of attrition bias, either due to a higher drop‐out rates in the treatment compared to placebo arms or specific mention of participant study withdrawal due to hypoglycaemia . Six studies were found to have a high risk of bias for selective reporting, either for providing only a range of hypoglycaemia outcomes or reporting hypoglycaemia data only for the extension phase or insufficient details on the severity of episodes …”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for white- and Asian-dominant groups for SGLT-2i. See references 50 65 for complete citations. …”
Section: Resultsmentioning
confidence: 99%
“…Также не учитывалась возможность повышения дозы ипраглифлозина с 50 мг до 100 мг в день. Это допущение было основано на том, что в РКИ, в которых изучалась эффективность и безопасность ипраглифлозина при СД 2 типа, титрация ипраглифлозина до 100 мг у пациентов, которым она была необходима, изучалась в основном во второй части исследования, которая проводилась как открытое исследование [13,14]. В единственном РКИ, где титрация дозы до 100 мг проводилась во втором периоде исследования при сохранении дизайна РКИ (пациентам, не достигшим уровня HbA1c < 7%, был добавлен ипраглифлозин 50 мг без ослепления, при этом была продолжена терапия, которую они получали исходно, с сохранением ослепления), статистически значимых изменений по среднему уровню HbA1c в группе, получавшей в результате ипраглифлозин в дозе 100 мг, выявлено не было, хотя еще 12% пациентов (9 из 69 в данной группе) достигли уровня HbA1c < 7% 9 .…”
Section: Discussionunclassified
“…В 2019 году был зарегистрирован новый препарат, относящийся к иНГЛТ-2 -ипраглифлозин. Его эффективность и безопасность в монотерапии и в комбинации с другими сахароснижающими препаратами была продемонстрирована в ряде исследований [5][6][7][8][9][10][11][12][13][14]. Включение данного препарата в перечень жизненно необходимых и важнейших лекарственных препаратов (ЖНВЛП) потенциально может расширить возможности доступа пациентов с СД 2 типа к данной группе препаратов.…”
unclassified